Rocket science unveiled: A differential equation exploration of motion - Pravesh Sharma; Suresh Kumar Sahani; Kritika Sharma; Kameshwar Sahani (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Through the perspective of differential equations, the report